Parliamentary Interpreting in Malaysia: A Case Study - Ibrahim, Noraini (Meta, 2009)
AbstractThis article seeks to describe the current scenario of parliamentary interpreting in Malaysia by studying the interpreters’ work nature, aptitude and qualifications as well as remuneration and promotional opportunity. It also highlights the important aspects of the profession such as job mystification, training and continuing education, the connection between the training centres and the professional environment, the need to educate the public through the establishment of professional associations, and the implementation of an ethics code as well as the sense of professionalism among the interpreters. The author also proposes ways to improve the situation which would contribute to the professionalisation of interpreting in the Malaysian Parliament particularly and in Malaysia in general.